Investigating the Influence of Mass Media on Cosmetics Usage among Women in Kashan during 2015 - Rouhullah Dehghani; Rezvan Talaee; Mojtaba Sehat; Narges Nikkhah Ghamsari; Leila Mesgari (Iranian Journal of Health, Safety and Environment, 2017)
The use of cosmetics is very common among women in Iran. Given the importance of the use of mass media and the impact on the consumption of cosmetics, this study attempted to consider the influence of mass media on the use of cosmetics among women in Kashan. Using a standard designed questionnaire, the data were obtained from 800 women. Multi-stage cluster sampling was randomly carried out. The data were analyzed using SPSS statistical software. The findings showed that 59.9% of the participants believed that satellite programs have the greatest impact on the use of cosmetics. 33% of the participants who believed that mass media had significant influence in this regard; they had a constant tendency to use cosmetics. Mass media advertisements encourage women to consume cosmetics; therefore, introducing the real and appropriate cultural models via advertisements on mass media may have positive impacts on women to consume cosmetics properly.